Hemophilia and child abuse as possible causes of epidural hematoma: case report Hemofilia e abuso infantil como possíveis causas de hematoma extradural: relato de caso - Fernando Campos Gomes Pinto; Fabrizio Frutos Porro; Liliana Suganuma; Ricardo Bragança de Vasconcellos Fontes; Almir Ferreira de Andrade; Raul Marino Jr (Arquivos de Neuro-Psiquiatria)
INTRODUCTION: Head trauma is an important consequence of child abuse. Specific pathophysiological mechanisms in child abuse are responsible for the ''whiplash shaken-baby syndrome'', which would favour the occurrence of intracranial hemorrhages. CASE REPORT: We report the case of a child who developed epidural hematoma following minor-intensity head trauma. Initial diagnosis of child abuse was made, but subsequent investigation led to the diagnosis of hemophilia A. CONCLUSION: Even though epidural hematoma is not closely associated with child abuse, this aethiology must always be considered when the reported trauma mechanism is out of proportion to the magnitude of the encountered lesions. INTRODUÇÃO: Traumatismo crânio-encefálico é importante conseqüência de abuso infantil. Mecanismos fisiopatológicos específicos do abuso infantil são responsáveis pela ''whiplash shaken-baby syndrome'', o que favoreceria o aparecimento de hemorragias intracranianas. RELATO DE CASO: Relatamos o caso de uma criança que desenvolveu hematoma extradural após trauma de pequena intensidade. Foi feito diagnóstico inicial de abuso infantil, mas investigações subseqüentes levaram ao diagnóstico de hemofilia A. CONCLUSÃO: Embora o hematoma extradural não esteja intimamente relacionado com abuso infantil, esta etiologia deve ser sempre considerada quando o mecanismo de trauma relatado estiver fora de proporção com as lesões encontradas.